Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Team Game Tournament (Tgt) Pada Muatan Pelajaran Pendidikan Pancasila Materi Hak Dan Kewajiban Kelas Iii Sdn 52 Kota Bengkulu - Agusdianita, Neza; Yuliarti, Komang Ratna; Mediana, Via; Nurhasanah, Nurhasanah; Purnamasari, Wina; Bela, Mielanda Dwi Putra (Universitas Dehasen Bengkulu, 2025)
Based on observations of the learning outcomes of class III students at SDN 52 Kota Bengkulu in the Pancasila Education lesson content, it is very low, learning is teacher-centred and students do not participate actively, so improvements in learning are needed. The aim of this research is to improve the learning outcomes of class III students at SDN 52 Bengkulu City using the Team Games Tournament (TGT) learning model. The implementation of this learning improvement is Classroom Action Research (PTK) consisting of 3 cycles, the stages of each cycle are planning, implementation, observation and reflection. The research subjects were 7 class III students at SDN 52 Bengkulu City for the 2024 academic year. The data analysis technique used quantitative analysis. The research results show an increase in learning outcomes, students participate actively in learning.